A systematic review of trends and findings in research employing drawing assessment in science education. Issue 1 (2nd January 2020) - Chang, Hsin-Yi; Lin, Tzung-Jin; Lee, Min-Hsien; Lee, Silvia Wen-Yu; Lin, Tzu-Chiang; Tan, Aik-Ling; Tsai, Chin-Chung
ABSTRACT: In this study, we reviewed 76 journal articles on employing drawing assessment as a research tool in science education. Findings from the systematic review suggest four justifications for using drawing as a type of research tool, including assessment via drawing as (a) an alternative method considering young participants' verbal or writing abilities, and affective or economic reasons, (b) a unique method that can reveal aspects not easily measured by other methods, (c) a major method that reflects characteristics of science subjects, and (d) a formative assessment to diagnose students' ideas to benefit their learning. Furthermore, five research trends of studies using drawing as assessment tools are identified, including: (a) students' conceptions of scientists from the Draw-a-Scientist-Test (DAST) and evolving studies, (b) students' understanding or mental models of science concepts, (c) participants' conceptions of science learning or teaching, (d) students' inquiry abilities and modelling skills via drawing, and (e) technology to support drawing. For each trend, we synthesised and commented on the current findings. A framework conceptualising phases and issues when designing research and instruments employing drawing assessments is proposed. The review provides insights into the design and future direction of research employing drawing assessments in science education.